Pelatihan Bioteknologi Es Krim Tape Singkong sebagai Peluang Wirausaha Masyarakat Desa Baturappe Kabupaten Gowa - Riska Amriani; Salmiah Hardianty; Sutireski Ibrahim; Nurhayani H. Muhiddin (JKM: Jurnal Kemitraan Masyarakat, 2023)
Baturappe Village is one of the areas with potential natural resources. The majority of the population work as farmers. One of the most abundant agricultural products in this area is cassava. People usually process cassava into fermented food, namely tape. Through the Biotechnology Product Entrepreneurship Training work program, KKN-T UNM Team provides biotechnology training on processing cassava tape into ice cream products that are in great demand by the community, especially among children. The main purpose of this activity is to foster innovation and creativity in processing agricultural products and provide entrepreneurial opportunities for the community. This activity was held on Monday, October 24, 2022 at the Baturappe Village Office, Biringbulu District, Gowa Regency. This activity was attended by Baturappe village community leaders consisting of SMPN 4 Biringbulu teachers, village head women, hamlet head women Posyandu cadres, and PKK members. The results of the activity showed the enthusiasm of the community participate in the training so that they could recognize the biotechnology process of making cassava tape into ice cream. The community has insights and knowledge about modern entrepreneurship and the community is enthusiastic about developing entrepreneurship by processing cassava into advanced products that are nutritious and have economic value.